Ijtihad sebagai Dasar Penetapan Hukum dalam Jual Beli Digital: Analisis Fiqh terhadap E-Commerce - Bina Prima Panggayuh; Kayla Baskya Aurelia; Pramita Dianni Rahayu; Asri Aryu Ningsih; Sevila Maulida Ayogi (Moral : Jurnal kajian Pendidikan Islam, 2025)
The rapid development of e-commerce as part of the broader digital transformation has introduced various new forms of transactions that were not explicitly recognized in classical Islamic jurisprudence. These include digital contracts, non-physical goods, cloud-based services, and electronic payment systems. Such innovations present a range of legal challenges, particularly concerning the validity of contracts, the legal status of digital products, the permissibility and security of electronic payment methods, and the protection of consumers in online transactions. To address these challenges, Islamic scholars have increasingly turned to ijtihad the process of independent reasoning and interpretation—as a methodology capable of providing legal solutions for contemporary issues. This study employs a qualitative approach, primarily through literature review, to examine the foundational principles of ijtihad, various methodological tools, and their applicability to different aspects of e-commerce transactions. The findings demonstrate that ijtihad methods, including qiyās (analogical reasoning), istislāh (consideration of public interest), istihsān (juridical preference), and ‘urf (customary practice), enable Islamic law to remain adaptive and flexible, while still oriented toward justice and public welfare. By applying these methods, Islamic jurisprudence can provide legal certainty, uphold fairness, and ensure that e-commerce practices align with Shariah principles, ultimately fostering trust and ethical behavior in the digital marketplace.